Liberating Bicycles in Niki Caro’s Whale Rider and in Haifaa Al Mansour’s Wadjda - Hambuch, Doris (Imaginations)

(untitled) (York University, 2019)
Susan B. Anthony declared in 1896 that the bicycle “has done more to emancipate women than anything else in the world.” The comparative study of Whale Rider (2002) and Wadjda (2012) demonstrates that this liberating effect of the basic tool of transportation is being reinforced in the new millennium. The analysis further situates two contemporary women filmmakers, Niki Caro from New Zealand and Haifaa Al Mansour from Saudi Arabia, within the growing global network Patricia White identifies, in Women’s Cinema, World Cinema (2015), as crucial for the improvement of female directors’ conditions in a global film industry.